Randomized Trial of Bilateral versus Single Internal-Thoracic-Artery Grafts. - Taggart, D; Altman, D; Gray, A; Lees, B; Gerry, S; Benedetto, U; Flather, M; ART Investigators (Massachusetts Medical Society, 2016)
Background: The use of bilateral internal thoracic (mammary) arteries for coronary-artery bypass grafting (CABG) may improve long-term outcomes as compared with the use of a single internal-thoracic-artery plus vein grafts. Methods: We randomly assigned patients scheduled for CABG to undergo single or bilateral internal-thoracic-artery grafting in 28 cardiac surgical centers in seven countries. The primary outcome was death from any cause at 10 years. The composite of death from any cause, myocardial infarction, or stroke was a secondary outcome. Interim analyses were prespecified at 5 years of follow-up. Results: A total of 3102 patients were enrolled; 1554 were randomly assigned to undergo single internal-thoracic-artery grafting (the single-graft group) and 1548 to undergo bilateral internal-thoracic-artery grafting (the bilateral-graft group). At 5 years of follow-up, the rate of death was 8.7% in the bilateral-graft group and 8.4% in the single-graft group (hazard ratio, 1.04; 95% confidence interval [CI], 0.81 to 1.32; P=0.77), and the rate of the composite of death from any cause, myocardial infarction, or stroke was 12.2% and 12.7%, respectively (hazard ratio, 0.96; 95% CI, 0.79 to 1.17; P=0.69). The rate of sternal wound complication was 3.5% in the bilateral-graft group versus 1.9% in the single-graft group (P=0.005), and the rate of sternal reconstruction was 1.9% versus 0.6% (P=0.002). Conclusions: Among patients undergoing CABG, there was no significant difference between those receiving single internal-thoracic-artery grafts and those receiving bilateral internal-thoracic-artery grafts with regard to mortality or the rates of cardiovascular events at 5 years of follow-up. There were more sternal wound complications with bilateral internal-thoracic-artery grafting than with single internal-thoracic-artery grafting. Ten-year follow-up is ongoing.